Escaping the exchange of information: Tax evasion via citizenship-by-investment - Dominika Langenmayr; Lennard Zyska (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
With (automatic) exchange of tax information among countries now common, tax evaders have had to find new ways to hide their offshore holdings. One such way are citizenship-by-investment programs, which offer foreigners a new passport for a local investment or a fixed fee. We show analytically that high-income individuals acquire a new citizenship to lower the probability that their tax evasion is detected through information exchange. Using data on cross-border bank deposits, we find that deposits in tax havens increase after a country starts offering a citizenship-by-investment program, providing indirect evidence that tax evaders use these programs.
Keywords: H26; H24; F53; K37; 330; Citizenship-by-investment programs; tax havens; tax evasion